Prevalence of Posttraumatic Stress Disorder and Depression Among Internally Displaced Persons in Mogadishu-Somalia - Ali M; Mutavi T; Mburu JM; Mathai M (Neuropsychiatric Disease and Treatment, 2023)
Mustafa Ali, Teresia Mutavi, John Maina Mburu, Muthoni Mathai Department of Psychiatry, University of Nairobi, Nairobi, KenyaCorrespondence: Mustafa Ali, Department of Psychiatry, School of Medicine, College of Health Sciences, University of Nairobi, P.O. Box 19676-00200, Nairobi, Kenya, Email mustafxabeeb@gmail.com; mustafa@student.uonbi.ac.keBackground: Nearly 2.6 million people have been forced into displacement camps in Somalia as a result of frequent conflicts exacerbated by climate change disasters. Although the psychological impact of war and natural disasters is well documented elsewhere, little is known about the unseen scars of psychological trauma among internally displaced persons (IDPs) in Somalia. This study was carried out between January and February 2021 and sought to determine the prevalence of post-traumatic stress disorder (PTSD) and depression among IDPs and examine the association between displacement and these psychiatric conditions.Methodology: A cross-sectional quantitative study was conducted among 401 IDPs in Mogadishu. The Harvard Trauma Questionnaire was used to determine the levels of trauma exposure and PTSD, and Hopkins Symptom Checklist-25 was used to estimate the prevalence of depression. Multivariate and bivariate analyses were performed to analyze the association between demographic and displacement variables and the outcomes of PTSD and depression.Results: More than half (59%) of participants met the symptom criteria of depression, and nearly a third (32%) of respondents met the symptom criteria for PTSD. The most prevalent traumatic event was a lack of food or water (80.2%). Important predictive factors for the development of psychiatric morbidity were unemployment, cumulative traumatic exposure, and frequency and duration of displacement.Conclusion: The study revealed high levels of depressive disorder and PTSD among IDPs in Mogadishu. Furthermore, this study provided evidence of IDPs’ susceptibility to trauma exposure and lack of essential services and goods. The study highlighted the importance of the provision of Mental Health and Psychosocial Support (MHPSS) services in IDP camps.Keywords: trauma, depression, PTSD, Somalia, IDPs